Magnetovolume anomalies in Ce2 Fe17-x Mn x - Prokhnenko, O.; Arnold, Z.; Kamarad, J.; Medvedeva, I.; Kuchin, A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2001)
The small nonmonotonic changes of the lattice parameters upon the substitution of Mn for Fe inCe2Fe17 lead to significant changes of the magnetic properties. In order to determine the role of thevolume, we made ac susceptibility and thermal expansion measurements on the polycrystalline compoundsCe2Fe16.65Mn0.35 and Ce2Fe16Mn1 under hydrostatic pressure up to 10 kbar in the temperature range 10-300 K. The substitution of Mn for Fe leads to significant narrowing of the range of stability of the low-temperature ferromagnetic phase characterized by Q T =48 K (x=0.35) in comparison with binary Ce2Fe17, where Q T =94 K. Applying a relatively small pressure of 1.5 kbar leads to suppression of both the ferromagnetic order and large positive spontaneous volume magnetostriction in Ce2Fe16.5Mn0.35. The pressure effect on Q T is significant, dQ T / dp=-30 K/kbar. The effect of pressure on the Néel temperature is moderate and slightly increases with increasing Mn content(dT N / dp= -2.2 K/kbar for Ce2Fe16.65 Mn0.35). No ferromagnetic order was observed in Ce2Fe16Mn1 at ambient pressure, but an unexpected reentering increase of the ac susceptibility was detected at pressures higher than 1.5 kbar below 50 K. It indicates the existence of a pressure-induced ferromagnetic phase at low temperature. The results show not only a strong correlation between the magnetic properties and the lattice volume but also a significant role of the Mn content.